Autoidentyfikacje współczesnej młodzieży – przyczynek do dyskusji na temat: Młodzież, czyli kto? - Myszka, Lucyna (Kultura-Społeczeństwo-Edukacja, 2013)
Modern youth, forced to live in complicated and unpredictable reality, faces the task of building its own identity and nding its own auto identi cation. This article is an analysis of this subject, based on research conducted by the author. It tries to nd an aswer to questions like „who is modern youth”, „how does it present itself and shape its own self image” and „how does modern youth percieve the surrounding reality”.